Short- and Long-Term Effects of High-Intensity Interval Training vs. Moderate-Intensity Continuous Training on Left Ventricular Remodeling in Patients Early After ST-Segment Elevation Myocardial Infarction—The HIIT-EARLY Randomized Controlled Trial - Eser, Prisca; Trachsel, Lukas D.; Marcin, Thimo; Herzig, David; Freiburghaus, Irina; De Marchi, Stefano; Zimmermann, Andreas J.; Schmid, Jean-Paul; Wilhelm, Matthias (Frontiers in Cardiovascular Medicine, 2022)
Aims Due to insufficient evidence on safety and effectiveness of high-intensity interval training (HIIT) in patients early after ST-segment elevation myocardial infarction (STEMI), we aimed to compare short- and long-term effects of randomised HIIT or moderate-intensity continuous training (MICT) on markers of left ventricular (LV) remodeling in STEMI patients receiving optimal guideline-directed medical therapy (GDMT). Methods Patients after STEMI (<4 weeks) enrolled in 12-week cardiac rehabilitation (CR) programme were recruited for this randomised controlled trial (NCT02627586). During a 3-week run-in period with three weekly MICT, GDMT was up-titrated. Then, patients were randomised to HIIT or isocaloric MICT for 9 weeks. Echocardiography and cardiopulmonary exercise tests were performed after run-in (3 weeks), end of CR (12 weeks) and at 1 year follow-up. Primary outcome was LV end-diastolic volume index (LVEDVi) at end of CR. Secondary outcomes were LV global longitudinal strain (GLS) and cardiopulmonary fitness. Results Seventy-three male patients were included, with time between STEMI and start of CR and randomisation 12.5±6.3 and 45.8±10.8 days, respectively. Mixed models revealed no significant group×time interaction for LVEDVi at end of CR. However, there was a significantly smaller improvement in GLS at one year follow-up in the HIIT compared to the MICT group (p=0.031 for group×time interaction). Cardiorespiratory fitness increased similarly in both groups. Conclusions In optimally treated patients early after STEMI, HIIT was not different from isocaloric MICT with regard to short-term effects on LVEDVi and cardiorespiratory fitness. The worsening in GLS at one year in the HIIT group deserves further investigation.